Association of Low Muscle Density With Deteriorations in Muscle Strength and Physical Functioning in Rheumatoid Arthritis. Issue 3 (25th February 2021) - Baker, Joshua F.; Mostoufi-Moab, Sogol; Long, Jin; Taratuta, Elena; Leonard, Mary B.; Zemel, Babette
Abstract : Objective: Rheumatoid arthritis (RA) is associated with low muscle density due to the accumulation of intramuscular fat. The present study was undertaken to identify predictors of changes in muscle density and to determine whether low muscle density predicted changes in strength and physical function. Methods: Patients with RA, ages 18–70 years, completed whole‐body dual‐energy x‐ray absorptiometry and peripheral quantitative computed tomography to quantify lean and fat mass indices and muscle density. Dynamometry was used to measure strength at the hand, knee, and lower leg. Disability and physical function were measured with the Health Assessment Questionnaire (HAQ) and the Short Physical Performance Battery (SPPB). Assessments were performed at baseline and at follow‐up. Regression analyses assessed associations between patient characteristics, muscle density, and deteriorations in strength and function. Results: Muscle density was assessed at baseline in 107 patients with RA. Seventy‐nine of these patients (74%) returned for a follow‐up assessment at a median follow‐up time of 2.71 years (interquartile range 2.35–3.57). Factors associated with declines in muscle density included female sex, higher disease activity, smoking, and lower insulin‐like growth factor 1 (IGF‐1) levels. Greater muscle density Z score at baseline (per 1 SD) was associated with less worsening per year according to HAQ, SPPB, and 4‐meter walk time scores and a lower risk of a clinically important worsening in HAQ score (odds ratio [OR] 1.90 [95% confidence interval (95% CI) 1.06, 3.42]; P = 0.03) and walking speed (OR 2.87 [95% CI 1.05, 7.89]; P = 0.04). Conclusion: Worsening of skeletal muscle density occurred in patients with higher disease activity, in smokers, and in those with lower IGF‐1. Low muscle density was associated with worsening of physical function. Interventions addressing reductions in muscle quality might prevent functional decline.